Communications of the Government of Surabaya In the Socialization Protocol Health through the Account of @sapawargasby - fitria widiyani roosinda (Jurnal Ilmu Komunikasi, 2021)
The government Surabaya city is one that uses Instagram as a forum for delivering information to the people of Surabaya, especially during crisis conditions like now, this research on this analysis aims to analyze the Instagram content of the Surabaya city government, namely @sapawargasby which is managed by the Surabaya Department of Communication and Information during the period. the beginning of the covid 19 pandemic to the mid-pandemic period. This @sapawargasby Instagram analysis research uses qualitative research methods, namely, using a case study method with discourse analysis techniques. Data collection was done secondary by means of screenshots / screenshots of Instagram account posts @sapawargasby for later analysis and drawing conclusions related to problem formulations. The results showed that the Surabaya city government was very active and creative in presenting information on Instagram, almost every day the @sapawargasby account posted everything about the policies or activities of the Surabaya city government, and in the early days of the pandemic, it was seen that the Surabaya city government was very responsive in making prevention and application of health protokols to inhibit the Covid-19 virus, not only that on Instagram, it also displays other policies that are very beneficial to the people of Surabaya, such as giving free seeds and deductions for building permits, even though in the middle of the pandemic there were several posts related to the covid virus 19 began to decrease, but the attention of the Surabaya city government is still clearly visible, the activeness and transparency of the Surabaya city government in utilizing social media technology, both imitated by governments in other regions.